PENGARUH MATA KULIAH KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA - Moh Saiful Anam; Endang Endang; Siti Alfiyana; Dimas Surya Atmaja; Dewi Fatmawati (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The interests of the business community are critical to social and economic growth. Because entrepreneurship fosters an atmosphere that encourages innovation and long-term economic growth, it also makes a country more competitive in the global marketplace. The aim of this research is to find out how entrepreneurship courses at the Faculty of Economics, Bojonegoro University influence development economics students' interest in entrepreneurship. The research approach offered uses quantitative descriptive analysis methods. The number of samples in this study was 75 people, and the original data was in the form of a questionnaire with a Likert scale for measurement. Based on research findings, although the application of this course does not have a real impact on company interests, from an understanding perspective, it has a significant and positive influence on the entrepreneurial interest of development economics students at the Faculty of Economics, Bojonegoro University. from students enrolled in the development economics curriculum, Faculty of Economics, Bojonegoro University.